2011
DOI: 10.1097/qad.0b013e328349c6ee
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir use and cardiovascular disease events

Abstract: This meta-analysis of RCTs does not support the hypothesis that ABC-containing cART regimens carry a greater risk of MI or major cardiovascular events relative to comparator cART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 40 publications
0
53
1
2
Order By: Relevance
“…Solid organ transplantation has not previously been recognized as a risk factor. However, a systematic review concluded that liver transplant patients receiving antifungal prophylaxis exhibited a reduction of episodes caused by C. albicans but had a higher proportion of C. glabrata infections (7). In this single-center study, exposure to antibacterial agents was a protective factor for candidemia caused by non-albicans Candida spp.…”
Section: Discussionmentioning
confidence: 78%
“…Solid organ transplantation has not previously been recognized as a risk factor. However, a systematic review concluded that liver transplant patients receiving antifungal prophylaxis exhibited a reduction of episodes caused by C. albicans but had a higher proportion of C. glabrata infections (7). In this single-center study, exposure to antibacterial agents was a protective factor for candidemia caused by non-albicans Candida spp.…”
Section: Discussionmentioning
confidence: 78%
“…Some additional studies have confirmed the increased risk described in the D:A:D [10,18,44,49,[54][55][56]; however, other studies have not found evidence of such association [47,48,[57][58][59][60] (Table 2).…”
Section: Nucleoside Reverse Transcriptase Inhibitors (Nrti's)mentioning
confidence: 75%
“…Recently, two additional meta-analyses and an observational cohort of subjects randomized to ACTG RCT did not find evidence of increased risk of CVD with abacavir exposure; however, the median age of patients included in the RCTs was significantly lower than in cohort studies [57,59,60].…”
Section: Nucleoside Reverse Transcriptase Inhibitors (Nrti's)mentioning
confidence: 92%
“…Possible cardiovascular toxicity of ABC in adults remains controversial. A meta‐analysis of RCTs did not find an increased cardiovascular risk 118 and the biological mechanism of possible cardiovascular toxicity of ABC has not been established. To date, no link to cardiovascular toxicity has been found in ABC‐exposed children.…”
Section: Drug Toxicities and Interactionsmentioning
confidence: 99%